The winter secret - Lulu Taylor (Pan Books, 2018)
My dear boy, the place is cursed. It always has been and it always will be . . .' Buttercup Redmain has a life of pampered luxury, living in beautiful Charcombe Park. Her older husband, Charles Redmain, is wealthy and successful, and proud of the house he has painstakingly restored, once owned by a famous ancestor. Buttercup is surrounded by people who make her life delightfully easy. But the one thing she really wants seems impossible. There are other discomforting realities: her husband's ex-wife Ingrid still lives nearby although Buttercup has never met her. And it soon becomes clear that all the people who make Buttercup's life so carefree are also watching her every move. Does she actually live in a comfortable but inescapable cage? And what is the real story of her husband's previous marriage? Xenia Arkadyoff once lived in Charcombe Park with her father, a Russian prince, and her mother, a famous film star. Life seemed charmed, full of glamour and beauty. But behind the glittering facade lay pain, betrayal, and the truth about the woman Xenia spent her life protecting. Now Charcombe Park is calling back people who were once part of its story, and the secrets that have stayed long hidden are bubbling inexorably to the surface . .